Percentage of Self-feeding Practice in Babies Using Baby-led and Traditional Weaning in Indonesia - Susmarini, Dian; Sumarwati, Made; Isworo, Atyanti; Latifah, Lutfatul (Jurnal Keperawatan Soedirman, 2019)
Introduction: Baby-led weaning is a new method of complementary food introduction for babies which enables babies to feed themselves. Over the last decade, the number of mothers adopting this method has been growing in many countries including Indonesia, though the exact number is unknown. The practice of self-feeding in babies using baby-led weaning in Indonesia also has not been identified.Aim: To identify self-feeding practices among babies in both baby-led and traditional weaning.Method: The study design was that of a descriptive survey given to a population of the mothers of six to 12-month-old babies who practiced either baby-led or traditional weaning in Indonesia. A consecutive sampling technique with time limit was used, and 316 respondents were recruited through an online survey.Results: Almost half of the baby-led weaning group practiced self-feeding at least 90% of their meals, whereas 80% of the traditional weaning babies practiced spoon-feeding at least 90% of their meals. The self-feeding percentage in the rest of the baby-led weaning participants, however, ranged from 10 to 75%. The type of family, who is appointed to take care of the baby, mother’s occupation, and engagement in family dining may contribute to the variations in self-feeding percentages.Conclusion: There was a difference in feeding practices between baby-led and traditionally weaned babies as assumed. The unique percentage of self-feeding among baby-led weaning in this country is useful as a reference for further research in this area.